Guidelines for the Management of Grown Up Congenital Heart Disease (GUCH) - Cilliers, Antoinette; Hugo-Hamman, Chris; Brown, Steven; Levin, Solly (SA Heart Journal, 2017)
Commentary by the Paediatric Cardiac Society of South Africa (PCSSA) on the European Society of Cardiology Guidelines for the “Management of Grown Up Congenital Heart Disease. The Task Force on the Management of Grown Up Congenital Heart Disease of the European Society of Cardiology.